PENGEMBANGAN MEDIA POP-UP BOOK KEBERAGAMAN BUDAYA JAWA TIMUR UNTUK MENINGKATKAN PENGETAHUAN KEBHINEKAAN PADA ANAK USIA DINI - Aini, Sarifah; Reza, Muhammad; Rakhmawati, Nur Ika Sari; Fitri, Ruqoyyah (TARBAWI:Journal on Islamic Education, 2025)
This research was conducted to overcome the problem regarding the use of learning media which is still insufficiently varied in increasing knowledge of diversity in early childhood. The importance of introducing cultural diversity from an early age to foster the character of respecting differences in children. The aim of the research is to determine the suitability of the media and determine the effectiveness of the East Java cultural diversity pop-up book media to increase knowledge of diversity in early childhood. This research uses a type of research and development with the ADDIE model (analyze, design, development, implementation and evaluation). Based on the tests that have been carried out, the results obtained are: 1) The media expert validation results obtained a score of 92.1% and the material expert validation results obtained a score of 95%, which means that the pop-up book media is included in the valid category and is very suitable for use. 2) The results of the effectiveness test, the Wilcoxon test using SPSS 25 obtained results <0.001 so that the results of significance were smaller than 0.05, so Ho was rejected and Ha was accepted. There is a difference between the average pretest and posttest which has an increase. Based on the results of the analysis, it was found that the pop-up book media on East Java's cultural diversity was effectively used to increase knowledge of diversity in early childhood.